Assessment of phenological, carpometric and yield allied attributes of olive cultivars harvested at different maturity stages - Alam, Riaz; Sajid, Muhammad; Kashif-Ur-Rahman (Journal of Pure and Applied Agriculture, 2023)
The phenological, carpometric and yield characteristics of olive cultivars: Frontoio, Manzanilla, Ottobratica, Pendolino and Picual were evaluated at different harvesting stages (Lemon green, Semi-ripe and Ripe) during 2014 and 2015 under irrigation condition at Olive Model Farm Sangbhatti, situated in Mardan-Pakistan (Latitude: 34°16ʹ21.32ʺN; Longitude: 72°18ʹ06.33ʺ and Altitude: 375 m). Pendolino started early flower opening on 12th April, taken as baseline for phonological attributes and took more days (9.50) to fruit set, while less days (6.33), started from 18th April were noted for Ottobratica. The cultivars Manzanilla and Picual attained lemon green maturity after 193.50 (25th October) and 192 (22nd October) days respectively, while 202.17 (2nd November) and 201.33 (1st November) days were taken by these cultivars to reach semi ripe stage and 214.17 and 210 days to ripe stage of harvesting respectively. Frontoio, Ottobratica and Pendolino attained semi ripe stage after 180.17 (11th October), 184.50 (20th October) and 193 (22nd October) days respectively, while 188 (19th October), 195 (30th October) and 203.67 (2nd November) days were taken by these cultivars to attain ripe stage of harvesting after flower opening. The cultivar Manzanilla produced heavy fruits (4.34 g), however large sized fruits (4.48 cm3 ) with more pulp: stone (4.94) were yielded by Picual. High fruit yield (35.81kg tree-1 ) and more oil percentage (14.66%) were determined in the oil extracted from fruits of Frontoio. Yield and yield components enhanced from lemon green to semi-ripe and ripe stage of harvesting, also the percentage of oil increased with the ripening process of olive fruits. Olive cultivars Frontoio, Manzanilla and Picual are recommended for high yield and production of olive oil. © 2021 Department of Agricultural Sciences, AIOU